2023
DOI: 10.3390/antiox12040820
|View full text |Cite
|
Sign up to set email alerts
|

Rutin Protects Fibroblasts from UVA Radiation through Stimulation of Nrf2 Pathway

Abstract: This study explores the photoprotective effects of rutin, a bioflavonoid found in some vegetables and fruits, against UVA-induced damage in human skin fibroblasts. Our results show that rutin increases cell viability and reduces the high levels of ROS generated by photo-oxidative stress (1 and 2 h of UVA exposure). These effects are related to rutin’s ability to modulate the Nrf2 transcriptional pathway. Interestingly, activation of the Nrf2 signaling pathway results in an increase in reduced glutathione and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Based on reports, we predicted an initial dose range from 0.001–10 μmol L −1 in cells, and verified this with an MTT test. 39–41 As shown in Fig. S4A,† the results indicated that it was safe for lung cells to be exposed to this concentration of rutin.…”
Section: Resultsmentioning
confidence: 81%
“…Based on reports, we predicted an initial dose range from 0.001–10 μmol L −1 in cells, and verified this with an MTT test. 39–41 As shown in Fig. S4A,† the results indicated that it was safe for lung cells to be exposed to this concentration of rutin.…”
Section: Resultsmentioning
confidence: 81%
“…A concentration titration curve was performed at 5, 10 and 25 μM to determine the better concentration of punicalagin pre-treatment. UVA exposure times were 1 and 2 h, based on our previous results ( Tabolacci et al, 2023 ). Thus, cell viability was assessed after treatment of fibroblasts with 5, 10 and 25 μM punicalagin and exposure to UVA irradiation for 1 and 2 h, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Under the same experimental conditions, non-exposed cells were kept alive for the same period of time. Based on the cell viability results and our previous study ( Tabolacci et al, 2023 ), we designed the next experiments in which the cells were exposed to UVA radiation for 1 or 2 h. Punicalagin (Sigma-Aldrich, P0023) was dissolved in DMSO to reach a concentration of 10 mM, and the solution was diluted to the appropriate amount in complete medium before use.…”
Section: Methodsmentioning
confidence: 99%
“…By scavenging free radicals, quercetin decreases the action of transcription factors that generate pro-inflammatory cytokines, often found elevated in patients suffering from chronic inflammatory diseases [ 47 ]. Rutin (3,30,40,5,7-pentahydroxyflavone-3-rhamnoglycoside) is often used in patients with capillary fragility, varicose veins, and hematomas, but recent papers have shown an important antioxidant effect [ 48 ]. These authors demonstrated rutin’s protective effect on fibroblasts when subjected to UVA radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species were measured (%) as fluorescence intensity after administration of rutin (10 µM) and subsequent exposure to UVA radiation for 1 and 2 h. In cells without rutin, the increase in ROS was 20% after 1 h of exposure and 200% after 2 h, whereas, in cells pre-treated with rutin, transmission levels were similar to those in cells not exposed to radiation. The authors concluded that rutin could significantly reduce ROS, evidencing its antioxidant effect [ 48 ].…”
Section: Resultsmentioning
confidence: 99%